Adding immersive virtual reality laboratory simulations to traditional teaching methods enhances biotechnology learning outcomes - Beatrice, Peter; Grimaldi, Annalisa; Bonometti, Stefano; Caruso, Enrico; Bracale, Marcella; Montagnoli, Antonio (Frontiers in Education, 2024)
Immersive virtual reality (VR) simulations are increasingly being used in diverse educational and training contexts to supplement traditional learning methods. The high versatility of virtual laboratories allows students to take advantage of many benefits, like experiencing dangerous reactions, time-consuming protocols, or expensive equipment without the necessity of a real science laboratory. However, little research is currently available to support the efficacy and efficiency of this new learning tool. In this context, the main objective of this study was to assess the influence of biotechnology training by using immersive VR technologies on the student's motivational and learning outcomes as compared with learning with conventional methods only. To this aim we tested two diverse strategies, respectively VR simulations were used in place of or in addition to the teacher's introductory lesson of a hands-on laboratory experience. Aligned questionaries were administered before and after the proposed activities to assess theoretical knowledge, self-efficacy, interest in biotechnology, and engagement of the participants. We found that when the introductory lesson to a biotechnology hands-on laboratory is replaced with an equivalent immersive VR simulation, the student's learning outcomes are lower with respect to the traditional approach. On the contrary, when VR simulations are integrated as an additional tool to the existing learning methods, higher learning outcomes were observed demonstrating a deeper understanding of the learning contents. Furthermore, our study showed that learning with immersive VR simulations motivates students more than the traditional methods, thus, using this new technology in addition to the existing educational methods in biotechnology could be considered as a win-win strategy to raise the attention of the students while increasing the learning outcomes.